2014
DOI: 10.1007/s13300-014-0084-9
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Clinical and Economic Outcomes of Liraglutide Versus Sitagliptin in Patients with Type 2 Diabetes Mellitus in the United States

Abstract: IntroductionThe objective of this study was to compare the clinical effectiveness of liraglutide with sitagliptin and assess the associated economic outcomes in patients with type 2 diabetes mellitus (T2DM) treated in real-world practice in the United States (US).MethodsThis retrospective cohort study used a large US claims database to identify patients with T2DM who initiated liraglutide or sitagliptin between January 2010 and December 2012. Adults (≥18 years old) with persistent use of therapy for ≥3 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 26 publications
(32 reference statements)
3
22
0
Order By: Relevance
“…Initiation of GLP‐1RA treatment at lower HbA1c levels was associated with better glucose control over 2 years of follow‐up. The observed HbA1c reductions were consistent with previous findings . While glycaemic achievements observed within 6 months of GLP‐1RA treatment initiation were higher in clinical trials, it is recognized that the effectiveness studies based on real‐world data generally provide lower estimates of glycaemic reduction or treatment effect(s) in general.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Initiation of GLP‐1RA treatment at lower HbA1c levels was associated with better glucose control over 2 years of follow‐up. The observed HbA1c reductions were consistent with previous findings . While glycaemic achievements observed within 6 months of GLP‐1RA treatment initiation were higher in clinical trials, it is recognized that the effectiveness studies based on real‐world data generally provide lower estimates of glycaemic reduction or treatment effect(s) in general.…”
Section: Discussionsupporting
confidence: 89%
“…A meta‐analysis of clinical trials conducted by Eng et al showed that the combination of a GLP‐1RA with basal insulin resulted in robust glycaemic control without increased risk of hypoglycaemia or weight gain. The effectiveness of adding GLP‐1RA to basal insulin therapy on glucose and weight control in patients with T2DM has also been evaluated in a number of observational and real‐world data‐based studies . The intensification of insulin therapy by addition of GLP‐1RA, rather than adding mealtime insulin, has been shown to be an attractive therapeutic option, and is now recommended in international guidelines: “The available data now suggest that either a GLP‐1 receptor agonist or prandial insulin could be used in this setting [in patients not achieving target glycated haemoglobin (HbA1c)], with the former arguably safer, at least for short‐term outcomes.”…”
Section: Introductionmentioning
confidence: 99%
“…Four additional publications have examined RW change in HbA 1c among patients treated with liraglutide, exenatide, sitagliptin, and DPP-4s as a class (37)(38)(39)(40); none of these examined the role of medication adherence, and the patient populations differed from our study and the previous study of medication adherence (10). Two of these studies selected patients that may bias toward patients more adherent than typical by requiring patients to have at least 3 months of fills and 6 months of follow-up (38,39). These two studies reported a change in HbA 1c of 21% to 20.9% for liraglutide, 0.68% for exenatide, and 0.63% for sitagliptin, similar to our findings among adherent RW patients, or a little lower in the case of exenatide (our study showed reduction of 0.86% for GLP-1s and 0.60% for DPP-4s).…”
Section: Discussionmentioning
confidence: 86%
“…Specifically, the NN2211-1860 (-LIRA-DPP-4) trial comparing the efficacy and safety of liraglutide versus sitagliptin demonstrated a greater lowering of HbA1 c after 26 weeks and 52 weeks of treatment with liraglutide [6,7]. Additionally, multiple observational studies have confirmed greater reductions in HbA1 c and a higher likelihood of achieving glycemic endpoints with liraglutide versus sitagliptin during a 6-month assessment [8][9][10][11]. A recent real-world study has also highlighted the longterm effectiveness of liraglutide in this population [12].…”
Section: Discussionmentioning
confidence: 99%
“…The class of incretin-based therapies, including glucagon-like peptide-1 receptor agonists (GLP-1 RAs) and dipeptidyl peptidase 4 (DPP-4) inhibitors, may allow for improved control of hyperglycemia and offers important advantages to an older population (i.e., minimal risk for hypoglycemia, weight loss, and lower risk for cardiovascular disease associated with GLP-1 RAs) [5]. Previous studies have found that the GLP-1 analogue liraglutide provides sustained glycosylated hemoglobin (HbA1 c ) reduction, achievement of specific HbA1 c goals, and weight loss when compared to the DPP-4 inhibitor sitagliptin [6][7][8][9][10][11][12]. Additionally, retrospective observational studies have demonstrated the cost-effectiveness of liraglutide when compared within and between antidiabetic drug classes; however, cost-effectiveness has not been specifically explored in a T2D population aged 65 years and older [11,[13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%